Simultaneous spectrophotometric determination of methyldopa and hydrochlorothiazide in pharmaceutical dosage form by AUC and first order derivative method - V.B Bharkad; H.N Khan; A. G Mangulkar; MD Zameeruddin; S.V. Jadhav; Prakash Katakam (International Journal of Pharmacy and Analytical Research, 2022)
A New, Simple, Accurate And Sensitive UV-Spectrophotometric Method has been developed for simultaneous determination of Methyldopa And Hydrochlorothiazide(HCTZ) in bulk And combined dosage form .Method A is AUC method, which involved measurement of area between 276-286nm and 266-276nm for the estimation of MD and HCTZ respectively. Method B Applied first order derivative Spectrophotometry, which involved measuring the absorbance values at 271.40nm and 251.20nm of first derivative spectrum. Beer’s law obeyed in concentration range of 10-60µg/ml and 2-14µg/ml for MD & HCTZ respectively by both Methods. Results of analysis were statistically reported & were found to be satisfactory.